High-performance radio frequency passive devices on plastic substrates for radio frequency integrated circuit application - Hung, Bing-Fang; Chen, Chia-Chung; Kao, Hsuan-Ling; Chin, Albert (My University, 2007)
High-performance passive RF devices were fabricated on insulating plastic substrates. These passive devices included inductors, low-loss coplanar waveguide (CPW) and microstrip transmission lines, 30 GHz narrow-band filters, and 25 GHz CPW ring resonators. The characteristics of these devices agreed well with those of ideal devices, as predicted by electromagnetic simulations.
Keywords: RF; plastic; inductor; filter; ring resonator